SUMBER STRES, STRATEGI KOPING, GEJALA STRES, DAN KEPUASAN PERKAWINAN PADA ISTRI BEKERJA - Fala, Maulidia; Sunarti, Euis; Herawati, Tin (Jurnal Ilmu Keluarga dan Konsumen, 2020)
Wives who work in the public sector have increased every year in both formal and informal occupations. This study aims to analyze the differences and effects of stress sources, coping strategies, and stress symptoms on marital satisfaction in working for married families. This study uses a cross-sectional study design. Research respondents are wives who work in the formal-informal sector, intact families, and are willing to be involved in the research. Withdrawal of respondents using probability sampling methods and disproportional stratified random sampling techniques with respondents totaling 120 (n = 65 formal) and (n = 55 informal). The results showed that age, length of education, per capita income, sources of stress, coping strategies, and marital satisfaction with wives with formal occupations had higher mean values. Large family, length of the marriage, long hours of work, length of workdays, and symptoms of stress on wives with informal types of work have a higher average value. Marriage satisfaction is significantly positively influenced by coping strategies and negatively affected significantly by stress symptoms. Job characteristics (the type of work, length of work hours, length of workdays) have an indirect effect on marital satisfaction.